Climate change, marriage and health - Chuang, Jie-Yu; Capellan, Joel Alfredo (Frontiers in Climate, 2025)
Few studies to date have examined the triadic relationship between climate change, marriage dynamics, and health. This review will investigate the speculated causal pathway originating from climate change, influencing marriage rates, and ultimately resulting in adverse health outcomes. We first summarize climate-health links, marriage-health links, then the sparse literature on the climate-marriage link; before offering a conceptual framework for future work. Due to the nascent nature of this research area, there is a lack of a unified perspective on these matters. More research is warranted to explore the public health implications of climate change and increasing singlehood. Furthermore, policy adjustments can be tailored to the research findings. For example, distinct public health policies could be applied to men and women if future studies show a significant sex difference in the proposed causal pathway.